Synthesis of cyclodextrin polymers containing glutamic acid and their use for the synthesis of Ag nanoparticles. (15th December 2018) - de Souza, Viviane Costa; Barros, Caio H.N.; Tasic, Ljubica; Gimenez, Iara F.; Teixeira Camargo, Zaine
Highlights: β-CD crosslinked with citric acid polymer was functionalized with glutamic acid. A novel polymer consisting of β-CD crosslinked with glutamic acid was obtained. The polymers were used as both reductant and stabilizer in the synthesis of AgNPs. The AgNP synthesis was environmentally friendly and easy. Abstract: Crosslinking and functionalizing agents play crucial roles in the properties/applications of cyclodextrin polymers. Here we report the synthesis of water-insoluble cyclodextrin polymers containingl -glutamic acid. In a first route, β-cyclodextrin was crosslinked with citric acid and subsequently functionalized withl -glutamic acid, while a second route involved esterification of β-cyclodextrin withl -glutamic acid, catalyzed by tin octoate. Combined evaluation by FTIR, 13 C CP/MAS NMR and elemental analysis indicated that the sample from the first route had the largest fraction of glutamic acid. Sorption tests with methyl orange showed that the cyclodextrin cavities were slightly more available in the polymer obtained through the second route. Samples were employed as reductant and stabilizer for fast and easy synthesis of silver nanoparticles at room temperature. Brief UV irradiation was sufficient for samples produced by the first route.